Horses as a Cognitive Psychological Vision in Stating Scenes -Zaid al-Khayl as a Model - Natiq Alwan, Malath; Kahdim Sahal, Dailam (International Journal of Psychosocial Rehabilitation, 2020)
Zaid al-Khayl is a poet whose name is associated with horses specifically, not out of nowhere about, his relationship with this beautiful animal, which is authentic, rises to the level of love that we prepare among lovers and perhaps the stating scenes we have shown. But unconventionally, you’re in contact with cognitive psychology, the best proof of what we’re saying. All of them came to give us a noble and bright image of that animal, which sings to the Arabs, old and new, but Zaid al-Khayl is completely different. The horse is only a lone wolf in the desert of the Arabian Peninsula, and its noble qualities are no less important than those of a noble man. They pushed it to be a reflective image of Zaid al-Khayl and even the horses of other knights, if there are any qualities in it, whatever they take. When Zaid leaves the earth to rise to heaven, he finds no better than the bird of punishment, the undisputed master of his name, too. A reflective image of his horse from here; the image of the horse is large and deep, the distance between the punishment of heaven and the wolf of the earth. As he moves into the world of materialism, he does not seem to confine the images of his dear horses between the two strongest and most contradictory elements of nature: fire and water.